CHALLENGES ENCOUNTERED BY AN ACTIVE BILINGUAL CHILD IN PRODUCTIVE SKILLS - Putu Devi Mas Wulandari; Ni Putu Era Marsakawati; Ni Luh Putu Eka Sulistia Dewi; Made Hery Santosa (UIBU, 2022)
The aim of this study was to describe the abilities and difficulties of bilingual children in speaking and writing in English and Bahasa Indonesia. A case study was used to design this research. The subject of this research was an 11-year-old, who communicated in both Bahasa Indonesia and English. Through observation, interview, videotaping of the child speaking English and Bahasa Indonesia, and document analysis, data were gathered. The result showed that the subject was an active bilingual child because he actively spoke Bahasa Indonesia as his mother tongue and English as his second language. In English speaking, he had constraints in pronouncing /wɑː.zənt/, /bɑːt/. In speaking Bahasa Indonesia, he missed spelling some words, such as Hari, Dermaga, Bermain. In, writing English, he had difficult in writing words. He dominantly had challenge in writing the Indonesian Language, especially in developing content, vocabulary used, and in grammar used.